2005
DOI: 10.1037/0022-0663.97.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Guidance, Reflection, and Interactivity in an Agent-Based Multimedia Game.

Abstract: The authors investigated whether guidance and reflection would facilitate science learning in an interactive multimedia game. College students learned how to design plants to survive in different weather conditions. In Experiment 1, they learned with an agent that either guided them with corrective and explanatory feedback or corrective feedback alone. Some students were asked to reflect by giving explanations about their problem-solving answers. Guidance in the form of explanatory feedback produced higher tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
2
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(225 citation statements)
references
References 33 publications
11
205
2
7
Order By: Relevance
“…It was more successful than receiving a justification for the simulation outcome or no further request to deal with the simulation results. Similar findings were obtained by Moreno and Mayer (2005), who showed the effectiveness of justifying the simulation outcome. Self-explanations can be induced by describing and interpreting one's own simulation outcome biologically.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was more successful than receiving a justification for the simulation outcome or no further request to deal with the simulation results. Similar findings were obtained by Moreno and Mayer (2005), who showed the effectiveness of justifying the simulation outcome. Self-explanations can be induced by describing and interpreting one's own simulation outcome biologically.…”
Section: Discussionsupporting
confidence: 75%
“…Further experimental support can be given by describing and justifying the simulation outcome. A study by Moreno and Mayer (2005) indicated higher domain-specific knowledge acquisition as a result of justifying one's own simulation outcome.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In fact, it can be argued that most educational games too often resemble digital exercise books and do not utilize the power of games as interactive context-free media. The reason for this may be that the field of educational technology lacks research on how to design game environments that foster knowledge construction and deepen understanding (Moreno & Mayer, 2005) and problemsolving while engaging and entertaining the user at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that adaptive guidance had a positive effect on the nature of trainees' study and practice, quality of their self-regulatory processes, knowledge acquired, performance, and performance adaptation. Moreno and Mayer (2005) examined the effects of guidance in an agent-based multimedia game.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…As Blake and Scanlon (2007, p. 2) state, these findings suggest, "Simulations do not work on their own, there needs to be some structuring of the students' interactions with the simulation to increase effectiveness." Indeed, a number of recent studies have shown that Simulation-Based Training 16 adaptive advice and various types of support can help guide individuals through simulations and enhance learning outcomes (Bell & Kozlowski, 2002a;Leutner, 1993;Moreno & Mayer, 2005;Reid et al, 2003;Reiber, Tzeng, & Tribble, 2004). However, as we discuss later, additional research is needed to better understand the amount and type of guidance needed for trainees to leverage the learner control inherent in simulation-based training.…”
Section: Simulation-based Training 15mentioning
confidence: 99%